2011
DOI: 10.1103/physrevb.83.035115
|View full text |Cite
|
Sign up to set email alerts
|

Conservation laws, integrability, and transport in one-dimensional quantum systems

Abstract: In integrable one-dimensional quantum systems an infinite set of local conserved quantities exists which can prevent a current from decaying completely. For cases like the spin current in the XXZ model at zero magnetic field or the charge current in the attractive Hubbard model at half filling, however, the current operator does not have overlap with any of the local conserved quantities. We show that in these situations transport at finite temperatures is dominated by a diffusive contribution with the Drude w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
286
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(295 citation statements)
references
References 83 publications
9
286
0
Order By: Relevance
“…On the other hand, the studies of Ref. [12] show that transport at finite temperatures is dominated by a diffusive contribution, the spin stiffness being very small or zero. Such studies exclude the large spin stiffness found in Ref.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the studies of Ref. [12] show that transport at finite temperatures is dominated by a diffusive contribution, the spin stiffness being very small or zero. Such studies exclude the large spin stiffness found in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…However, the isotropic point at ∆ = 1 (the spin-1/2 XXX model) [33] is the most experimentally relevant for the spin-lattice relaxation rate and other physical quantities [12,22,23]. It is also the case that poses the most challenging technical problems for theory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is important to note that D(t) yields no information beyond the mere width of density profiles. It is also worth pointing out in that D(t) addresses the overall dynamics and does not distinguish between transport channels with potentially different behavior [84,85].…”
Section: Diffusionmentioning
confidence: 99%
“…Some insight can be gained from effective low-energy theories such as bosonization [41][42][43], which is, however, limited to very low temperatures and may not correctly capture effects due to integrability without fine-tuning of parameters. An exact diagonalization study observed strong anomalous finitesize effects in σ reg (ω) of integrable Mott insulators [38], while many studies conclude that the dc conductivity…”
Section: Introductionmentioning
confidence: 99%